"Writing as Politics", Women and the Future: Issues and Strategies12.04.1987., Ferguson Center, University of Alabama, USA - Gjurgjan, Ljiljana Ina (1987)
The lecture has stressed the political importance of women’s writing, in particular its ability to destabilize the male metaphysical space and the stereotype presentations of women in male narratives.